Metode Pembelajaran Dalam Perspektif Alqur’an Dan Hadits - Suwarin Rais Nusi; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Method is the most important element in the Islamic education learning process. Because methods are among the determining factors for the success or failure of education and learning. And it would be good if the learning methods were appropriate and relevant to the needs and conditions of students in the learning process. The output in Islamic education is the confirmation that students must have the ability to understand, believe and practice Islamic teachings as a concrete result of the learning process. And to make this happen, learning methods in Islamic education must be based on primary sources, namely the Koran and the Hadith of the Prophet SAW which have been tested for validity with current developments. Islamic education learning methods that can be applied according to the perspective of the Qur'an and Hadith include: the method of bil hikmah, example, stories, ibrah or mau'izah, habituation or habituation, parables, punishment and reward, lectures, discussions or dialogue and jidal or debate, question and answer, demonstration, and practice or repetition. In essence, the Qur'an or Hadith is a solution in the process of human life that must be studied and understood in order to achieve its essence in living human nature as a servant of Allah SWT.